Reimagining citizenship in electoral times: Lessons from Gen Z’s digital civics prototypes for Indonesia’s 2024 election - Wawan Sobari (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This study examines how the Indonesian Generation Z reimagines the role of citizenship in electoral democracy by developing 11 digital civic prototypes for the 2024 election. This study used Schreier's Qualitative Content Analysis method on prototype documents developed by students of the Political Science Study Program at Brawijaya University. The analysis maps three dimensions of Marshallian rights civil, political, and social and the Westheimer-Kahne citizen typology, adding the categories of digital acts and connective action. The results showed a paradigm shift in citizenship from passive voters to participatory citizens through transparent access to candidate information, online channels for public aspirations, and discussion forums for political deliberation. The majority of prototypes emphasize digital-political literacy and the inclusion of young, first-time, and out-of-town voters by utilizing simple language, infographics, and interactive social media campaigns, including elements of gamification and peer mobilization typical of Gen Z. Dimensions of democratic ethics such as anti-abstention education and anti-money politics are quite strong, but social justice orientation and representation of marginalized groups are relatively weak. These findings confirm that the reimagining of citizenship practised by Gen Z in Indonesia focuses on expanding inclusive and ethical electoral access and participation while also revealing the need to strengthen the justice-oriented dimension of citizenship so that civic tech innovation can serve as a more equitable democratic infrastructure. This study provides conceptual and practical implications for educators, policymakers, and election organisers to adopt a collaborative, literacy-based, youth-friendly civic technology approach.